2023
DOI: 10.1007/s00464-023-09980-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluid management and vasopressor use during colorectal surgery: the search for the optimal balance

Abstract: Background Although it is known that excessive intraoperative fluid and vasopressor agents are detrimental for anastomotic healing, optimal anesthesiology protocols for colorectal surgery are currently lacking. Objective To scrutinize the current hemodynamic practice and vasopressor use and their relation to colorectal anastomotic leakage. Design A secondary analysis of a previously published prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Multivariate analysis also showed that phenylephrine use was associated with a higher risk of anastomotic leak compared to noradrenaline with an odds ratio of 4.2. 10 It is thought that vasopressors lead to vasoconstriction, deterioration of microcirculation, and potentially result in local tissue hypoxia. 11 These findings are consistent with those of older studies.…”
Section: Anemia and Tissue Hypoxiamentioning
confidence: 99%
“…Multivariate analysis also showed that phenylephrine use was associated with a higher risk of anastomotic leak compared to noradrenaline with an odds ratio of 4.2. 10 It is thought that vasopressors lead to vasoconstriction, deterioration of microcirculation, and potentially result in local tissue hypoxia. 11 These findings are consistent with those of older studies.…”
Section: Anemia and Tissue Hypoxiamentioning
confidence: 99%
“…On the other hand, fluid overload may result in harmful "third space" weight gain, associated with higher rates of pulmonary complications, postoperative ileus, altered mental status, and edema-related anastomotic complications, thus impeding postoperative recovery [12][13][14][15][16]. Furthermore, an excessive extracellular fluid volume may lead to abdominal compartment syndrome, which by itself may trigger adverse physiologic effects such as respiratory failure and renal failure [17].…”
Section: Introductionmentioning
confidence: 99%